Some Results on Certain Symmetric Circulant Matrices - Ramakrishna, A. V.; Prasanna, T. V. N. (Journal of Informatics and Mathematical Sciences, 2015)
A direct method for nding the inverse of a class of symmetric circulant matrices is given in [4]. In this paper a method of nding the Moore-Penrose inverse for a class of singular circulant matrices is presented and the spectral norm and spectral radius are calculated. Finally the spectral norm and spectral radius for symmetric circulant matrices with binomial coecients are derived.